Serum Transferrin Saturation Increase Is Associated With Decrease of Antibacterial Activity of Serum in Patients With HFE-Related Genetic Hemochromatosis - Jolivet-Gougeon, Anne; Loréal, Olivier; Ingels, Anne; Danic, Bruno; Ropert, Martine; Bardou-Jacquet, Edouard; Aqodad, Nourdin; Aussant-Bertel, Françoise; Ferec, Claude; Brissot, Pierre (The American journal of gastroenterology, 2008)
Patients with type 1 (HFE-related) genetic hemochromatosis are usually excluded from blood donation on the basis that this disease may facilitate bacterial infections. The aim of the present study was to evaluate the serum antibacterial effect against Salmonella enterica Typhimurium LT2 in relation to iron status. Serum samples were collected in 26 iron-overloaded (homozygous C282Y mutation) and 35 iron-depleted hemochromatosis patients and 33 healthy control subjects. The antibacterial activity of sera and iron parameters were tested for each patient. Serum from normal controls had an antibacterial effect against Salmonella Typhimurium LT2. The antibacterial effect decreased from the 1:2 to the 1:8 dilution and was always significantly lower in the iron-overloaded group. In both control and iron-depleted patients, a positive correlation was found between the decrease of antibacterial effect and the increase of both serum iron and transferrin saturation. These results (a) support the view that chronic iron overload decreases serum antibacterial effect against Salmonella enterica Typhimurium LT2, (b) favor the interest of including, besides serum ferritinemia, serum transferrin saturation levels as a further criterion for iron-depletive treatment efficacy, and (c) provide an argument for not discouraging the use of blood from iron-depleted hemochromatosis patients for transfusion.